Successfully Negotiating in Asia - Kim Cheng Low, Patrick; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Successful negotiation requires a close understanding of their partner$1 (Bs culture, their feelings, habits and values. When planning to do business with suppliers and other partners in Asia, a thorough preparation is essential to avoid misunderstandings, confrontations and disappointments, and to ensure the mutually desired success. This book presents a complete communication and negotiation skills program with special focus on negotiation partners from the different regions of the Asian continent. Readers learn to negotiate the Chinese, the Indian or the Japanese way, and they learn to understand the ways Asians negotiate. Written by a cross-border author, both academician and practitioner, with plenty of experience from Eastern and Western cultures, this book is a valuable resource for anyone relying on business success with Asian partners.s
Keywords: Economics; Industrial management; Business planning; Economics/Management Science; Management/Business for Professionals; Organization/Planning.